ผลกระทบของการบังคับใช้พระราชบัญญัติควบคุมอาคาร พ.ศ.2522 ต่อการก่อสร้างอาคารขนาดใหญ่ในเขตเทศบาลนครเชียงใหม่ - ชัยวัฒน์ เชื้อสกุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research is to study the Impact of Enforcement the Building Control Act B.E.2522 Toward Large Building Construction in Chiang Mai City Municipality Area. The objectives of this study were 1) to study the impact of Enforcement the Building Control Act B.E.2522 effect to people and real estate entrepreneurs in Chiang Mai City Municipality Area. 2) to study the problems of citizens and real estate entrepreneurs in Chiang Mai Municipality to enforce the Building Control Act. 3) to study the problems of the enforcement of the Building Control Act to people, real estate owners and officers of Chiang Mai City Municipality such as architect, engineers and civil engineers those who play a role of design and building control in Chiang Mai City Municipality. The instrument of this study was data collection. Data were collected via questionnaire that included three parts as follows: Part 1: people in Chiang Mai City Municipality including people who have construction permits, renovation, and living nearby large/extra-large building. Part 2: real estate entrepreneurs divided into 3 groups 1. small scale 2. middle scale 3. large scale Part 3: Member of Chiang Mai City Municipality council, architect engineer and civil engineer, officer in Bureau of Public Works in Chiang Mai City Municipality, who is responsible for construction permits. The problems were found that the operating system license requirements were slow, a survey to verify construction or authenticate the conflicts of boundary was delay, the air pollution, dust problem, colour and chemical of construction and machinery noise pollution affected to people who live nearby. It was recommended that there should be integration of Building Control Act B.E.2522 and related laws (Building Control Act B.E.2535 and 2543) including rules or the Ministry of the Interior Law issued by local organization or authority, such provisions or notification of Bangkok Metropolitan Administration, provision or notification of the City Municipality, Town Municipality and the city of Pattaya according to under this Act and other legislations combined as a single law. That is the Building Construction Act in order to reduce the complexity of the laws or regulations.